International dispute settlement - Merrills, J. G. (Cambridge : Cambridge University Press, 2011)
"A guide to the techniques and institutions used to solve international disputes, how they work and when they are used. This textbook looks at diplomatic (negotiation, mediation, inquiry and conciliation) and legal methods (arbitration, judicial settlement). It uses many, often topical, examples of each method in practice to place the theory of how things should work in the context of real-life situations and to help the reader understand the strengths and weaknesses of different methods when they are used. It also looks at organisations such as the International Court and the United Nations and has been fully updated to include the most recent arbitrations, developments in the WTO and the International Tribunal for the Law of the Sea, as well as case law from the International Court of Justice" -- Provided by publisher
1. Negotiation -- 2. Mediation -- 3. Inquiry -- 4. Conciliation -- 5. Arbitration -- 6. The International Court I: organisation and procedure -- 7. The International Court II: the work of the Court -- 8. The Law of the Sea Convention -- 9. International trade disputes -- 10. The United Nations -- 11. Regional organisations -- 12. Trends and prospects
Includes bibliographical references and index
Keywords: Pacific settlement of international disputes